Analysis And Modelling Of Geoelectric Data Modeling For The Identication Of Groundwater aquifer At Cisarua Area, West Bandung - Daniswara, A; Dahrin, Darharta; Setianingsih, Setianingsih (Himpunan Ahli Geofisika Indonesia (HAGI), 2019)
Groundwater is the main need of society in everyday life. Groundwater is one of renewable resources but it doesn’t mean that it can be exploitated without limit. Several factors that affect the availability of groundwater derived from nature such as geological conditions, rainfall, and green areas should be considered. Water in the soil is stored in a porous layer and has a good permeability is called an aquifer. Cisarua area is located in West Bandung regency, West Java which is a hilly area that has a topography with a slope ranging from normal to steep. The land use in this area is still dominated with plantation and forest as green area. Groundwater aquifer characteristics in that area needs to be examined and analysed for the needs of the community and agricultural business. In this research, the writer used inversion modeling technique of geoelectric data to visualize the condition of subsurface. Resistivity inversion modelling of apparent resistivity data as a result of resistivity method with Wenner-Schlumberger configuration is then carried out with least-square method. The initial model is modified in an iterative manner such that the sum of square error of the difference between the model response and the observed data values is minimized. The result of resistivity modelling is used for analysis of aquifer characteristic such as lithology, depth and structure along with considering geological reference. As the result of modelling, the area of measurement is divided into three zones which are Zone of aeration, Zone of Saturation, and endapan formasi. Zone of aeration is located at depth 0-25 m with resistivity 20-100 Ohm.m and the predicted lithology is gravel or weathered soil. Zone of Saturation (akuifer) is located at depth 25-60 m with resistivity 4-30 Ohm.m and the predicted lithology is sandstone or clay. Endapan Formasi Cibereum is located at more than 60 m from ground with resistivity more than 100 Ohm.m and the predicted lithology is sandy tuff or dry breccia.